Principles of behavioral economics: Microeconomics & human behavior - Dhami, Sanjit (New Delhi Cambridge University Press, 2025)
Principles of Behavioral Economics, written by an acknowledged leader in the field, provides a comprehensive introduction to one of the most exciting areas of modern economics. It demonstrates how models of economic theory can be enriched by using interdisciplinary insights from psychology, sociology, evolutionary biology, and neuroscience to build the basis for a more empirically supported set of economic principles. Unique in its level of rigor and lucidity, the book highlights the important link between theoretical and empirical economics by demonstrating the usefulness of a range of data sources such as observational data, lab data, survey data, and neuroeconomic data. This field-defining textbook argues that behavioral economics is not just a supplement to mainstream economics.